Isolation, Identification and Detection of Listeria monocytogenes Persistence in Chicken Raw Meat Products and Comminuted Ready-To-Eat Sausages in Nelna Chicken Processing and Further Processing Plant (Pvt.) Ltd. Sri Lanka - Wickramasinghe, W.A.T.D.; Amarasingha, A.A.S.S.M. (University of Jaffna, 2021)
Listeria monocytogenes, a food borne pathogenic bacterium often isolated from meat and meat products, is considered a major causative agent responsible for serious diseases in both humans and animals. This study was carried out to determine the persistence rate and occurrence of L. monocytogenes in poultry meat and ready to eat sausages from Nelna Farm poultry meat processing plant, Meethirigala, Sri Lanka. A total of 100 samples were (50 samples of poultry meat and 50 samples of sausages) collected and tested for L. monocytogenes using Fraser Broth and HiCrome Agar Listeria medium, examined by ISO 11290 method and confirmed by biochemical tests (catalase, beta-hemolysis, CAMP test) and the motility test in semi-solid nutrient broth. Out of 100, only 13 samples were suspected as Listeria spp. by the colony appearance. After the biochemical tests, those 13 samples were also confirmed as not contaminated from L. monocytogenes. All the fifty chicken raw meat samples and fifty comminuted sausages samples from Nelna Farm were all negative for L. monocytogenes. As all the results are negative, some of the paired samples were sent to the Bureau Veritas, Colombo and those results were also negative. The samples are 100% free from virulent L. monocytogenes and also can conclude this factory has been following good hygienic practices based on hazard analysis and critical control point programs throughout the industry.
Keywords: Biochemical test; Isolation; Listeria monocytogenes; Poultry meat